Antibacterial activity of oenothera rosea (L 'Hér) leaf extracts - Gómez Flores, Ricardo Alberto; Reyna Martinez, Raul; Tamez Guerra, Patricia; Quintanilla Licea, Ramiro (2012)
Aims: To determine the antibacterial effect of Oenothera rosea against Escherichia coli, salmonella enteritidis and Vibrio cholerae. Study Design: In vitro antibacterial study. Place and Duration of Study: Universidad Autónoma de Nuevo León, Facultad de Ciencias Biológicas, Departamento de Microbiología e Inmunología and Departamento de Química, San Nicolás de los Garza, NL. México, from June 2010 to June 2011. Methodology: The antibacterial in vitro effect of methanol and aqueous extracts of the Mexican plant O. rosea against strains of E. coli, S. enteritidis and V. cholerae was evaluated in liquid medium by the colorimetric 3-[4,5-dimethylthiazol-2-yl]-2,5- diphenyltetrazolium bromide (MTT) reduction assay. Results: Methanol and aqueous extracts significantly inhibited growth of all bacterium strains tested. The methanol extract caused up to 55%, 66% and 87% growth against E. coli, S. enteritidis and V. cholerae, respectively, whereas the aqueous extract induced up to 54%, 69% and 88% bacterial growth inhibition, respectively. Methanol and aqueous vehicle controls did not alter bacterial growth. Conclusion: The observed antibacterial effect of O. rosea extracts may be of benefit as an adjuvant treatment of diseases caused by the studied enterobacteria.